2011
DOI: 10.1161/circulationaha.110.017012
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase-Type Plasminogen Activator Promotes Paracellular Transmigration of Neutrophils Via Mac-1, But Independently of Urokinase-Type Plasminogen Activator Receptor

Abstract: Background-Urokinase-type plasminogen activator (uPA) has recently been implicated in the pathogenesis of ischemia-reperfusion (I/R) injury. The underlying mechanisms remain largely unclear. Methods and Results-Using in vivo microscopy on the mouse cremaster muscle, I/R-elicited firm adherence and transmigration of neutrophils were found to be significantly diminished in uPA-deficient mice and in mice treated with the uPA inhibitor WX-340, but not in uPA receptor (uPAR)-deficient mice. Interestingly, postische… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 35 publications
4
34
0
Order By: Relevance
“…Furthermore, in GPIbα-deficient animals, collateral vessel walls displayed a reduction in urokinase-type plasminogen activator expression, which is linked to decreased leukocyte extravasation. 8,56 Our results are in line with recent observations in other inflammatory processes, such as venous thrombosis or myocardial infarction, demonstrating that the absence of platelet GPIbα results in reduced leukocyte accumulation and transmigration. 14,57 Hence, GPIbα-dependent interactions of platelets with leukocytes and the endothelium exert a dual function during collateral development, (1) supporting leukocyte recruitment and (2) facilitating leukocyte transmigration into the perivascular space.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in GPIbα-deficient animals, collateral vessel walls displayed a reduction in urokinase-type plasminogen activator expression, which is linked to decreased leukocyte extravasation. 8,56 Our results are in line with recent observations in other inflammatory processes, such as venous thrombosis or myocardial infarction, demonstrating that the absence of platelet GPIbα results in reduced leukocyte accumulation and transmigration. 14,57 Hence, GPIbα-dependent interactions of platelets with leukocytes and the endothelium exert a dual function during collateral development, (1) supporting leukocyte recruitment and (2) facilitating leukocyte transmigration into the perivascular space.…”
Section: Discussionsupporting
confidence: 91%
“…by guest www.bloodjournal.org From relevance of proteases in particular is still an issue of controversial debate. [11][12][13][14][15][16][17][18] In the present study, we sought to define whether and how serine proteases, which represent over one third of all known proteolytic enzymes, as well as MMPs, which form a class of enzymes specialized on the degradation of the extracellular matrix, 22 are involved in leukocyte migration to the site of inflammation. Using a model of sterile peritonitis, we found that migration of neutrophils to the inflamed peritoneal cavity was effectively prevented by the broad-spectrum serine protease inhibitor aprotinin as well as by the broad-spectrum MMP inhibitor GM-6001.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the role of proteases in particular for leukocyte migration remains an issue of controversial debate. [11][12][13][14][15][16][17][18] Over one third of all known proteolytic enzymes are serine proteases, which are characterized by the ability to hydrolyze the peptide bond of their substrates via a nucleophilic serine residue in the active site. Among these enzymes, plasmin is one of the most prominent members regarding its elementary function in the fibrinolytic system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[8][9][10][11][12] In the context of I/R, the single components of the fibrinolytic system are increasingly recognized as individual and autonomous mediators: Plasmin has been demonstrated to contribute to leukocyte infiltration of reperfused tissue largely via its proteolytic properties, 14 whereas the serine protease urokinase-type plasminogen activator has been shown to regulate postischemic leukocyte responses independently of its proteolytic properties via receptor-mediated processes. 15 Recently, it has been reported that also tPA is critically involved in the pathogenesis of I/R injury. [16][17][18][19] The underlying mechanisms remained largely unclear.…”
mentioning
confidence: 99%